Pengaruh Model Pembelajaran Word Square terhadap Hasil Belajar Tema 1 Sub Tema 1 Kelas 5 Di MI Nurul Huda - Azizah, Ani Habibatul; Awaliyah, Bella Riska; Lestari, Siti Lilik (Mitra PGMI: Jurnal Kependidikan MI, 2022)
There are still many teachers who do not use interesting learning methods, as a result students become passive in learning. Teachers should use interesting methods and take advantage of existing facilities so that students are interested and enthusiastic about learning, The code square learning model affects students' learning. Analysis using word square as a test is proved this. The study was conducted at mi nurul huda sukaraja with the number of 60 students, classes a 30 and class b 30 respondents. The objectives of this study: 1. The learning outcomes of students who apply the word square learning model to the theme 1 sub-theme 1, 2. The learning outcomes of students who do not apply the word square learning model to the sub-theme 1 theme, 3. The effect of applying the word square learning model to friends 1 sub-theme 1. The research method used in this study is a quasi-experimental design with a true experimental design. This research can be concluded that the Word Square learning model has an effect on student learning outcomes